Influence of Different Pretreatments on Hot air and Microwave-Hot Air Combined Drying of White Sweet Cherry - Meric Simsek; Özge Süfer (Turkish Journal of Agriculture: Food Science and Technology)
Microwave (MW)-hot air (HA) combined drying was applied to white sweet cherries besides solely HA drying at 50, 60 and 70°C in the presence of citric acid, sucrose and freezing pretreatment in this study. Single power level of MW (90 W) was chosen, and drying behavior of all samples was modelled by using eleven thin layer equations. Two-term, rational and sigmoid models were the most suitable models for describing drying phenomena. Effective moisture diffusivities (Deff) ranged from 1.724×10-10 to 5.173×10-10 m2/s in HA drying and from 4.260×10-10 to 1.805×10-9 m2/s in MW-HA drying. Activation energies (Ea) were between 2.785 and 30.541 kJ/mol and 6.929 and 42.101 kJ/mol for HA and MW-HA drying techniques, respectively. Total color change (ΔE) levels of the outer surface of dried cherries were generally higher than the ones of inner surface. Freezing pretreatment had a comparably lower enhancing effect on the total phenolic content (TPC) of HA dried white sweet cherries compared to fresh sample. The TPC of freezing pretreated and HA dried at 50°C and HA dried at 70°C control samples were 1.481 ± 0.398 mg gallic acid equivalent (GAE)/g dry matter (DM) and 6.181 ± 0.012 mg GAE/g DM as the minimum and maximum, respectively. These values were determined as 4.183 ± 1.728 and 8.240 ± 0.502 mg GAE/g DM that were belonged to MW-HA dried at 50°C control and freezing pretreated MW-HA dried at 70°C samples in combined procedure, respectively.